PRECAUTIONS ARE BETTER THAN CURE: A GUIDELINE FOR POLICY MAKING TO COMBAT AGAINST THE VIRUS WITH THE REFERENCE TO DEVELOPING COUNTRIES - Sultan, MF; Shamsi, AF; Shaikh , S (Proceeding of the International Conference on Arts and Humanities, 2023)
Monkeypox is a form of zoonosis that was mostly transmitted through animals. However, in recent times research evidences several cases of secondary transfer all over the globe. Therefore, after the emergency situation was declared by the World Health Organization on the 22nd of May the probability of reemergence of the disease is much high. Therefore, there is a need to evaluate major predictors of monkeypox with reference to the developing sides of the world as the threat of an outbreak is much higher on developing sides of the world. This study has been done purposively to evaluate predictors of monkeypox with reference of Pakistan to evaluate the predictors with respect to their perceived impact numerically. SPSS has been used to reflect the importance of every predictor to support the policy formulation and improvement of precautionary measures to combat effectively the potential threat of the monkeypox virus.